Long-term monitoring of Sgr A* at 7 mm with VERA and KaVA. Issue Volume 9:Issue S303(2013) (22nd May 2014) - Akiyama, K.; Kino, M.; Sohn, B.; Lee, S.; Trippe, S.; Honma, M.
Abstract: We present the results of radio monitoring observations of Sgr A* at 7 mm (i.e. 43 GHz) with the VLBI Exploration of Radio Astrometry (VERA), which is a VLBI array in Japan. VERA provides angular resolution on millisecond scales, resolving structures within 100 Schwarzschild radii of Sgr A*, similar to the Very Large Baseline Array (VLBA). We performed multi-epoch observations of Sgr A* in 2005 - 2008, and started monitoring it again with VERA from 2013 January to trace the current G2 encounter event. Our preliminary results in 2013 show that Sgr A* on mas scales has been in an ordinary state as of August 2013, although some fraction of the G2 cloud already passed the pericenter of Sgr A* in April 2013. We will continue monitoring Sgr A* with VERA and the newly developed KaVA (KVN and VERA Array).